2016
DOI: 10.1038/srep27184
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of thioredoxin from the desert lichen-forming fungus, Endocarpon pusillum Hedwig, reveals its role in stress tolerance

Abstract: Endocarpon pusillum is a lichen-forming fungus with an outstanding stress resistance property closely related to its antioxidant system. In this study, thioredoxin (Trx), one of the main components of antioxidant defense systems in E. pusillum (EpTrx), was characterized and analyzed both in transgenic yeasts and in vitro. Our analyses identified that the heterologous expression of EpTrx in the yeast Pichia pastoris significantly enhanced its resistance to osmotic and oxidative stresses. Assays in vitro showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…An enhanced tolerance of strain TPX1 to high concentration of salt was just as expected, which showed similar results with some related Prxs [29, 30]. This finding is of great significance to reducing the costs for scale-up of ethanol production.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…An enhanced tolerance of strain TPX1 to high concentration of salt was just as expected, which showed similar results with some related Prxs [29, 30]. This finding is of great significance to reducing the costs for scale-up of ethanol production.…”
Section: Resultssupporting
confidence: 86%
“…However, when 3 mM of H 2 O 2 was added to the plates, TPX1 achieved a much better growth status than the strain 423, which indicated that the gene KmTPX1 might increase the tolerance of S. cerevisiae to H 2 O 2 . Similarly, a kind of 2-Cys Prxs from Oryza sativa [29] and the thioredoxin from Endocarpon pusillum [30] both have been proved to enhance the tolerance of S. cerevisiae to peroxides, including H 2 O 2 and 2-methyl-1,4-naphthoquinone (MD).
Fig. 2Effects of KmTPX1 overexpression on the growth behavior under oxidative stress.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of detoxification enzymes in cell protection has been well-documented in other plants (Sappl et al, 2009; Das and Roychoudhury, 2014), as well as the roles of proteins such as nucleoredoxin, multidomain thioredoxin, and ferritin (Kang and Udvardi, 2014; Li and Wei, 2016). In this study ferritins were found to be upregulated in the drought-stressed plants, potentially in order to sequester free iron that would otherwise catalyze the Fenton reaction and produce highly reactive hydroxyl radicals.…”
Section: Discussionmentioning
confidence: 99%
“…As dominant species, Endocarpon pusillum Hedw. has been intensively studied from many aspects, such as physiology under desiccation and starvation stress 10 , photosynthetic rate 11 , genome 12 , transcriptome 13 and stress resistance functional protein 14 . And all the above results supported that Endocarpon pusillum has good drought resistant ability, which could be one potential species used in the prospective ‘desert biocarpet engieering’ (DBCE) 15 , which has been proposed by Wei 16 , referring to developing during a short period into a dominant protection system instead of the naked desert with the help of the artificial inoculation of the microorganisms.…”
Section: Introductionmentioning
confidence: 99%